(untitled) (Research, Society and Development, 2021)
There are many challenges to dimension and implement a sewage collection network, the main one being the compatibility with the other networks existing on the street. To minimize this problem, the Building Information Modeling (BIM) methodology can help, as it is capable of generating a virtual model equivalent to the real one that can be visualized in 3D and simulated. Although this technology has been available on the market for years, it is still in its infancy when applied to infrastructure projects. The present work aimed to represent a sanitary sewage project through the Civil 3D software, which uses the BIM methodology, where the procedures for the creation of the network were detailed and the longitudinal, quantitative and descriptive profiles of the structures were generated. The use of the program was extremely efficient for the representation and compatibility of infrastructure projects.